Phytochemical content, antibacterial, antioxidant and cytotoxic activities, of leaves extracts of Eucalyptus globulus, Peltophorum africanum and Vangueria infausta - Portia Mamothaladi Moshidi; Johnfisher Mupangwa; Claude Mukengela Muya; Soul Washaya (Discover Agriculture)
Abstract This study aimed to determine the extraction yield, phytochemical content, antibacterial, antioxidant, and cytotoxic activities of leaves extracts from Eucalyptus globulus, Peltophorum africanum, and Vangueria infausta. Leaves were harvested, separated from the stems, and dried for chemical analysis. Crude and oil extraction, antioxidant activity, cytotoxicity, and minimum inhibitory concentration were determined, and tannins, flavonoids and alkaloids were quantified by standard protocols. The phenolic, flavonoids, and condensed tannin contents were higher (P < 0.05) in V. infausta extract than in E. globulus and P. africanum. The radical scavenging activities were higher (P < 0.05) in V. infausta, E. globulus than in P. africanum. The antibacterial activity was lower (P < 0.05) for P. africanum and E. globulus oil, and was strongly related to the presence of phenolics and flavonoids. The lack of toxicity of plant extracts suggests that extracts can be used as animal feed additives with no risk of toxicity. Vangueria infausta, Eucalyptus globulus had the highest antioxidant capability and can thus modulate nutrient metabolism in animals.